2013
DOI: 10.1038/labinvest.2013.91
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional changes in a new animal model of Ménière's disease

Abstract: The purpose of this study was to clarify the underlying mechanism of vertiginous attacks in Ménière's disease (MD) while obtaining insight into water homeostasis in the inner ear using a new animal model. We conducted both histopathological and functional assessment of the vestibular system in the guinea-pig. In the first experiment, all animals were maintained 1 or 4 weeks after electrocauterization of the endolymphatic sac of the left ear and were given either saline or desmopressin (vasopressin type 2 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
5
22
0
Order By: Relevance
“…Understanding the mechanisms underlying the pathophysiology of cochlear microcirculation is of fundamental clinical importance for Ménière's disease. The etiopathogenic role of vasopressin imbalance in the stria vascularis affecting microcirculation was recently elucidated in experimental animal models [Egami et al, 2013;Kakigi, 2013], becoming a promising target of new etiologic therapies [Naganuma, 2013]. Obstruction of the distal part of the vein of the vestibular aqueduct in experimental animals causes disturbances in the endolymph homeostasis and potentially symptoms similar to the ones of Ménière's disease [Friis and Qvortrup, 2007], confirming previous observations in humans affected by Ménière's disease who presented with occlusion of the vein of the vestibular aqueduct.…”
Section: Discussionsupporting
confidence: 75%
“…Understanding the mechanisms underlying the pathophysiology of cochlear microcirculation is of fundamental clinical importance for Ménière's disease. The etiopathogenic role of vasopressin imbalance in the stria vascularis affecting microcirculation was recently elucidated in experimental animal models [Egami et al, 2013;Kakigi, 2013], becoming a promising target of new etiologic therapies [Naganuma, 2013]. Obstruction of the distal part of the vein of the vestibular aqueduct in experimental animals causes disturbances in the endolymph homeostasis and potentially symptoms similar to the ones of Ménière's disease [Friis and Qvortrup, 2007], confirming previous observations in humans affected by Ménière's disease who presented with occlusion of the vein of the vestibular aqueduct.…”
Section: Discussionsupporting
confidence: 75%
“…Recently investigated reasons for SEH include traumatic injury, such as post-operative trauma following cochlear implantation (46) and stapedectomy for otosclerosis (7); ablation of the endolymphatic sac (8,9); and acoustic and mechanical trauma (2). Medications, including vasopressin (1,8), have also been associated with development of SEH.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the secretary function seems to be dominant in the AVP-V2R-AQP2 axis of the inner ear. Further, the degree of AVP-induced hydrops becomes more pronounced by the obstruction of the ES with the absorption function [6]. Although EH is confirmed to manifest within one hour after a one-shot subcutaneous injection of AVP [109], longitudinal development of AVPinduced EH is not yet well-documented.…”
Section: Hormonal-induced Endolymphatic Hydropsmentioning
confidence: 97%
“…It is likely that vertiginous attack presented by Uchida et al was caused by abrupt over-production of endolymph resulting from histamine-induced elevation of p-AVP level [5]. Indeed, Egami et al, made clear the role of vasopressin in the endolymph homeostasis and its close contact with inner ear function; administration of desmopressin (a VP type 2 receptor agonist) can exacerbate EH because of acute V2 (vasopressin type 2 receptor)-mediated effects, and, when combined with ES dysfunction, can cause temporary vestibular abnormalities that are similar to the vertiginous attacks in patients with MD [6]. Recently, Kim et al also confirmed that this application of the vasopressin type 2 receptor agonist in experimentally-induced EH produced asymmetric vestibular dysfunction in bidirectional sinusoidal harmonic acceleration test, similar to bidirectional nystagmus in MD [165].…”
Section: Vertiginous or Dizzy Attackmentioning
confidence: 99%
See 1 more Smart Citation